Multimedia Development in Guided Inquiry-Based Learning to Enhance Vocational High School Students' Computational Thinking Skills - Muhammad Akmaluddin Andayani Komara; Enjun Junaeti; Erna Piantari; Eka Fitrajaya Rahman (Pendidikan Komputer FKIP Universitas Lambung Mangkurat, 2025)
This study aims to develop multimedia-based learning using the Guided Inquiry-Based Learning model to enhance computational thinking skills among vocational high school students in the context of Society 5.0. The research adopts a Research and Development (R&D) approach following the ADDIE model and employs a one-group pretest-posttest design to evaluate its effectiveness. The developed multimedia integrates interactive educational games to support engagement and conceptual understanding. The results indicate a significant increase in students' computational thinking abilities, with average pretest and posttest scores improving from 41.30 to 67.83. The normalized gain scores show moderate improvement across computational thinking elements: decomposition (0.413), abstraction (0.283), pattern recognition (0.263), and algorithmic thinking (0.337). Student responses reveal an 82% satisfaction rate, categorized as